Актуализация проектно-исследовательской деятельности учащихся в образовательной практике начальной школы - Morozova N. A. (Modern education development: theory, techniques and practice, 2016)
The article considers relevant for the present stage of modernization of national education problem with the practice of introducing new GEF and change the paradigm of learning activity of schoolchildren. The author's position is the need to use in primary school education technology design and research activities of students, support for which is an effective means of developing the student as an active subject of the educational activity.
Keywords: проектная деятельность; реформа образования; образовательные технологии; учебная деятельность; проектно-исследовательская деятельность школьников; Educational technology; project activity; educational activity; the reform of education; project and research activity of schoolchildren